2018
DOI: 10.1650/condor-17-179.1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors and fisheries influence the foraging patterns of a subtropical seabird, the Westland Petrel (Procellaria westlandica), in the Tasman Sea

Abstract: Environmental and anthropogenic influences in the marine environment are primary drivers of behavior and demographic outcomes for marine birds. We examined factors influencing the foraging patterns of the Westland Petrel (Procellaria westlandica), a highly threatened, endemic petrel that inhabits subtropical water masses primarily in the Tasman Sea, with a poorly known at-sea distribution. Risk assessments place the species at moderate risk of population impacts from fisheries-related mortality. Studies in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(52 citation statements)
references
References 83 publications
3
47
2
Order By: Relevance
“…The present study confirmed and refined the chick-rearing movements of Westland petrels previously reported by at-sea observations [ 84 ] and tracking studies [ 45 , 48 ]. The species displayed restricted breeding movements (432 ± 20 km d –1 ) during the present study compared to the non-breeding movements (1351 km d –1 , [ 44 ]).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The present study confirmed and refined the chick-rearing movements of Westland petrels previously reported by at-sea observations [ 84 ] and tracking studies [ 45 , 48 ]. The species displayed restricted breeding movements (432 ± 20 km d –1 ) during the present study compared to the non-breeding movements (1351 km d –1 , [ 44 ]).…”
Section: Discussionsupporting
confidence: 91%
“…Data from 2016 and 2017 were gathered during the present study, data from 2012 and 2015 are from Waugh et al . [ 45 ]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations